Profil Sensori Produk Pangan Kering dengan Pemanfaaatan Tepung Ampas Kelapa dan Pati Sagu - Shanti Fitriani; Ayu Diana; Erpiani Siregar; Fikratul Ihsan; Masyitah; Fadlila Endyra; Ririn Oktavia Sitinjak; Dimas Wahyudi (Universitas Djuanda, 2026)
The potential of coconut pulp, which has not been optimally utilized, and the availability of sago starch in Riau Province presents a great opportunity for food product diversification. Food diversification can be carried out in snack bars and dry bread products. Sensory evaluation was conducted to determine acceptability, perceived quality attributes, and specific characteristics that arise from the use of coconut pulp flour and sago starch in the formulation. The objective of this study was to compare the sensory profiles of dry food products, namely snack bars and dry bread, with different coconut pulp flour and sago starch. A completely randomized design (CRD) with five treatments and four replicates was used. The results showed that coconut pulp flour and modified sago starch ratio (pregelatinization and HMT) had a significant effect on sensory attributes, especially brown color, while they had no significant effect on aroma, coconut pulp flavor, chewiness (snack bar), brittleness (dry white bread), or hedonic score. The best snack bar and dry bread treatments in this study were modified sago starch ratio and coconut pulp flour (80:20).